Identification of Genetic Relationship of Local Rice in East Java Based on gene matK - Putra, Kurniawan Setia; Listyorini, Dwi; Suharti, Suharti (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
Genetic diversity in living things is very important in the fulfillment of germplasm and conservation activities. East Java local rice is not so much cultivated farmers, so that the existence of local rice has begun to be replaced with new varieties and it is feared will happen genetic erosion of local rice. The purpose of this study to identify the genetic relationships of local rice and phylogenetic position of the rice contained in the Gene Bank. The method used to identify a molecular genetic using short pieces of DNA called DNA barcode. The results of this study indicate that the three local varieties of Berlian (Br), Genjah Harum (Gh) and Jawa (Jw) varieties can be identified by the matK gene barcode. The results of electrophoresis visualization showed that the DNA bands of the three samples were 900 bp. The results of DNA BLAST analysis show that the genetic relationships level with Oryza sativa and Oryza rufipogon is 100%. The results of the phylogenetic tree analysis showed that East Java's local rice was in one taxa with other rice and had a confidence level above 50